(untitled) (Dristikon: A Multidisciplinary Journal, 2021)
This article aims to explore the way Bharati Gautam’s memoir Vigata ra Baduli [Past and Hiccups] (2020) connects the writer with her homeland. Home and homeland are out of some major loci of diasporic life and the discourse. Diasporic writings deal with homeland both as a real place to return and an imaginary reality for those transnational migrants who have no chance of physical return to the place left back. To study the writer’s homeland connection as expressed in the book, this study uses qualitative methodology with its interpretative approach for analysis. The theoretical input is the diasporic discourse related to home and homeland. For the diasporans, homeland is the root of their life, culture, language and in total the life they live in the hostland. The time a diaspora loses its physical, imaginary or emotional connection with the homeland, it stops being a diaspora. Thus, every diasporic writing has some kind of homeland connection. The study finds that Gautam’s memoirs deal with her love and respect for the root. These feelings are expressed through her nostalgia, symbols and culture she follows in the USA. Similarly, her own and her children’s critical thoughts on Nepal and Nepali socio-cultural praxis also highlight their connection with the homeland. It is hoped that this study is useful to find how Nepali Diaspora connects itself with Nepal. It may encourage the researchers to work in this field.